Analysis and countermeasures of coal mine safety in Guizhou Province - SUN Guangyu, YANG Fuling, QI Chaoxin (Meikuang Anquan, 2021)
In order to carry out coal mine production scientifically, safely and efficiently, and improve the overall production level of coal mine safety in Guizhou Province, this paper applies statistical methods to carry out the analysis of coal mine safety status in Guizhou Province from the six aspects of “the status of coal mine safety accidents in the province”, “the nature and scale of coal mine enterprises”, and “the level of coal mine gas”, “coal seam spontaneous combustion level”, “coal dust explosion hazard”, and “coal mine hydrogeological conditions”. The main problems include “high levels”, “severe gas disasters and huge hidden of gas hazards”, “the greater threat of spontaneous combustion of coal seams”, “the higher risk of coal dust explosion”, and “the slightly higher risk of water hazards”. At the same time, in response to the main problems of coal mine safety in Guizhou Province, the countermeasures from three aspects of disaster prevention and control are “accelerate the adjustment of the coal industry’s structural system”, “establish a disaster prevention and control system that focuses on gas prevention and the prevention and control of other disasters”, and “pay attention to Bijie, Zunyi, Liupanshui, Anshun, southwest Guizhou.